Radikalisme dan Intoleransi terhadap Generasi Muda dalam Memanfaatkan Teknologi Era Globalisasi di Indonesia - Darmawan, Budi; Wijaya, Iqra Pandu; Alhuzaini, Muhammad (At-Tajdid : Journal of Islamic Studies, 2023)
The Radicalism and religious intolerance are issues that remain hot into the 21st century in Indonesia. The doctrine of radical and intolerant thinking can influence the diversity that Indonesia has, especially the spearheads of the nation such as the younger generation. Apart from that, technological developments are a new culture that lives in the era of globalization, so it does not rule out the possibility that the role of technology can influence the lives of religious communities in Indonesia. This article uses qualitative methods with descriptive analysis. Research sources were obtained from books, literature reviews, journals, legal regulations, laws, print media, the internet and so on. The analysis technique in this research uses a theory according to J. Toynbee, known as challenge and response theory. There are three data analysis techniques in this research, namely data reduction, data presentation and drawing conclusions. The research results show that radicalism and religious intolerance are cases that need to be anticipated in the era of globalization. The growing influence of technology among the younger generation has become a powerful weapon in the development of radicalism and religious intolerance in Indonesia. Therefore, further knowledge is needed regarding the benefits of technology in the era of globalization, for the younger generation amidst the rise of radicalism and religious intolerance